Relationship between vocabulary knowledge and reading comprehension among adult EFL Iranian students - Kameli, Shima (2012)
This study was performed with three main goals in mind. The first goal was to explore the relationship between two aspects of vocabulary knowledge (breadth/size and depth/quality) and also their relation with reading comprehension performance,individually. The second goal was to clarify the association among two components of vocabulary knowledge, i.e., breadth/size and depth/quality, with reading comprehension performance of EFL Iranian students on subtest of VLT, WAT and IELTS. Last but not least, the study also attempted to investigate the association of demographic variables (i.e., gender, age, field of study, educational level, outside activity, and kind of outside activity) and EFL Iranian students’ reading comprehension performance. At the beginning of second semester of 2010-2011 the quantitative data was collected from 220 EFL Iranian adult students (46 female, 174 male) who studied English in BAHAR Institute, Shiraz, Iran. To accomplish the purpose of this study, Background Questionnaire, Vocabulary Levels Test (VLT), Word Associates Test (WAT), and Reading Comprehension Test (IELTS) were administered in one session as research instruments. In general, the whole process of data collection took about five weeks during nine sessions. The respondents had a total time of 3 hours and 15 minutes to complete the three tests and the background questionnaire. Independent sample t-test, one-way ANOVA, two-tailed Pearson’s product moment correlations coefficient, and Multiple linear regression analysis were carried out to examine the associations and differences among predictors to predict reading comprehension performance. The analyzed results demonstrate that 1) different levels of vocabulary levels test were positively correlated, 2) test score on vocabulary size/breadth, depth/quality of vocabulary knowledge, and reading comprehension were also positively correlated, 3)vocabulary size/breadth was a stronger predictor of reading comprehension than depth/quality of vocabulary knowledge, 4) breadth/size and depth/quality of vocabulary knowledge were closely related one to another and mutually facilitative and also the significant relationship among vocabulary size and reading comprehension for the population tested were distinguished. In addition, the results revealed that gender, educational level, and having outside activity, had significant association with reading comprehension performance among demographic variables which, were considered in this study while the other variables namely age, field of study, and kind of outside activity had no significant correlation with the performance of reading comprehension.